Representasi Peran Ayah Sebagai Orang Tua Tunggal dalam Film Pendek “Mana Janji Ayah” (Semiotika Rolland Barthes) - Ani Gusliyani; April Laksana; Putri Handayani; Achmad Nashrudin; Meiby Zulfikar (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to determine the representation of the father's role as a single parent in the short film